From Farm to Firm : Rural-Urban Transition in Developing Countries - Dudwick, Nora (World Bank, 2012)
Around the world, countries are becoming urbanized at an astonishing pace. As countries develop economically, their economies shift from mainly rural and agrarian to increasingly urban and nonagricultural. This rural-urban transformation presents both opportunities and challenges for development. When managed effectively, the transformation spurs growth and reduces poverty. When managed poorly, however, the process can result in stark welfare disparities, the marginalization of entire regions, and poorly functioning cities that fail to realize the potential gains from agglomeration economies. This book investigates the rural-urban transformation underway in Sub-Saharan Africa and South Asia, emphasizing the influence of country conditions as well as the potential of good policies to minimize disparities and ensure that everyone shares in the benefits of urbanization. The first part of this book investigates urbanization and rural-urban welfare inequalities on three geographic scales global, national, and local featuring countries and cities in Sub-Saharan Africa on the national and local levels. The second part of the book sheds light on the texture of transformation in five countries in South Asia, each at a different stage in the process: Bangladesh, India, Nepal, Pakistan, and Sri Lanka.